The Brown paper school presents : the I hate mathematics! book - Burns, Marilyn, 1941-; Weston, Martha (Boston : Little, Brown, 1975)
Events, gags, magic tricks, and experiments to change one from a mathematical weakling into a mathematical heavyweight.
Includes index.
Book Links (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
6.8.
6.8
Keywords: Mathematics -- Juvenile literature; Mathematics; Mathematics